Knowledge base for education: an applicable framework in the didactic of probability (2017)
This article is classified in the research field of statistical education as far as the professional knowledge of the teacher is concemed; the elements of a theoretical firamework that makes it possible to inquire about the knowledge that the teacher possess, oriented to the teaching of probability at the level of pre-university education are presented by means of a content analysis carried out on various textual sources in order to establish such skills required by the teacher to guide the concept of probability within the mathematics curriculum in the aforementioned educational level; likewise, somo models of knowledge genesis are described under the paradigm of Shulman addressed to the teaching of mathematics and statistics, whit in certain contexts could be adapted to guie the learning of probability. finally a brief overview research associated whit the didactic of probability is offered.